2007
DOI: 10.2337/db06-1768
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Cbl-b Gene Enhances Infiltration and Activation of Macrophages in Adipose Tissue and Causes Peripheral Insulin Resistance in Mice

Abstract: OBJECTIVE-c-Cbl plays an important role in whole-body fuel homeostasis by regulating insulin action. In the present study, we examined the role of Cbl-b, another member of the Cbl family, in insulin action. RESEARCH DESIGN AND METHODS-C57BL/6(Cbl-b ϩ/ϩ ) or Cbl-b-deficient (Cbl-b Ϫ/Ϫ ) mice were subjected to insulin and glucose tolerance tests and a hyperinsulinemic-euglycemic clamp test. Infiltration of macrophages into white adipose tissue (WAT) was assessed by immunohistochemistry and flow cytometry. We exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 46 publications
2
58
0
Order By: Relevance
“…It is now generally accepted that chronic tissue inflammation is an important cause of insulin resistance in obesity (1,3,4) and that the proinflammatory tissue macrophage, particularly in adipose tissue, can be an initiating cell type in this inflammatory response (1,(7)(8)(9). In addition, we and others have shown that a specific subpopulation of macrophages, characterized by cell surface positivity for the markers F4/80, CD11b, and CD11c, accounts for the majority of the increased macrophage influx into adipose tissue (19,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now generally accepted that chronic tissue inflammation is an important cause of insulin resistance in obesity (1,3,4) and that the proinflammatory tissue macrophage, particularly in adipose tissue, can be an initiating cell type in this inflammatory response (1,(7)(8)(9). In addition, we and others have shown that a specific subpopulation of macrophages, characterized by cell surface positivity for the markers F4/80, CD11b, and CD11c, accounts for the majority of the increased macrophage influx into adipose tissue (19,28).…”
Section: Discussionmentioning
confidence: 99%
“…In both humans and rodents, macrophages (M) accumulate in adipose tissue (AT) with increasing body weight (2)(3)(4), and recent evidence implicates ATMs 2 as major contributors to tissue inflammation and insulin resistance in obesity (5,6). For example, mouse models have demonstrated that ATMs can be both necessary and sufficient (1,(7)(8)(9) for the development of insulin resistance in obesity. Specifically, disabling the inflammatory pathway within macrophages by creating myeloid cell-specific knockouts of IB kinase ␤ or JNK1 protected mice from diet-induced insulin resistance (5,6).…”
mentioning
confidence: 99%
“…In both humans and rodents, macrophages accumulate in adipose tissue with increasing body weight (Xu et al, 2003;Weisberg et al, 2003). Several rodent studies demonstrate that an increase in adipose tissue macrophages worsens insulin sensitivity (Hirasaka et al, 2007;Kamei et al, 2006). Likewise, a decrease in adipose tissue macrophages (ATM) results in a decrease in adipose tissue inflammation and inhibits obesity-induced insulin resistance (Patsouris et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence now converge on the notion that obesity causes low-grade chronic inflammation characterized by the recruitment of macrophages, T-cells, and neutrophils into the adipose tissue (2)(3)(4)(5). Among such inflammatory cells, the increase in adipose tissue macrophages (ATMs) 2 is associated with a further deterioration of adipose tissue inflammation and insulin sensitivity (6,7). In contrast, a decrease in ATMs in obese mice correlates with the amelioration of adipose tissue inflammation and insulin resistance (8,9).…”
mentioning
confidence: 99%